Improving efficiency of spinel structured catalyst for oxygen evolution reaction - Tan, Angeline Yan Jun (2019)
With the ever-rising demand for energy and the effects of global warming intensifies, we turned to renewable energy as our source of energy. Hydrogen energy is one of them. Hydrogen can be harnessed through the water splitting process. However, the limiting factor of water splitting process is the lack of an efficient oxygen evolution reaction (OER) catalyst. Thus, many researches have been investigating the different types of metal oxides, in search of an efficient OER catalyst. In this report, spinel structured metal oxides such as Zn0.5Mn2.5O4, MgxMn3-xO4, MgxNi3-xO4 and MgxCo3-xO4 were synthesised by sol-gel technique to evaluate their OER performances in alkaline conditions. At overpotentials of 360 mV (1.59 V vs RHE) and 370 mV (1.60 V vs RHE), Mg0.25Co2.75O4 electrode and Mg0.5Co2.5O4 electrode respectively recorded the highest OER performances among the other spinel metal oxides in this report at a current density of 10 mA cm-2. With a Tafel slope of 52 mV dec-1 and 51 mV dec-1, Mg0.25Co2.75O4 and Mg0.5Co2.5O4 respectively exhibited high stability in 0.1 M KOH solution. The stable and highly OER performances of MgxCo3-xO4 has exhibited high potential to be used in water electrolysers in alkaline media.